Shading of Africanized honeybees hives in Brazilian Semiarid - Santos, Ricardo Gonçalves; Domingos, Herica Girlane Tertulino; Gramacho, Kátia Peres; Gonçalves, Lionel Segui (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
In Northeast Brazil, beekeeping has an enormous growth potential, however, in most of this region, the climate is considered semi-arid with high levels of solar radiation, high temperatures and low rainfall intensity. This type of environment has caused many losses in honey production and generated enormous growth difficulties in the sector. Every year beekeepers lose many of their bee colonies because of the abandonment of hives (absconding behaviors), causing discouragement for beekeepers and thus the withdrawal of the practice of beekeeping. This study attempts to show through literature information that despite the negative influence of adverse environmental conditions in the Brazilian semiarid region, the shading of the hives is potentially effective to soften the harsh environmental conditions of the region. Swarms installed in beehives protected from direct sunlight perform the internal thermoregulation of the nest more easily, which would reflect a lower energetic cost of the bees and, therefore, higher yield of the colony. As result, it becomes the more productive and profitable process of rational creation of Africanized honeybees (Apis mellifera L.) in arid and semiarid regions. Shading can be considered a simple, efficient, and low cost technique for beekeepers, representing an economically viable alternative and cost-effective.